2020
DOI: 10.1111/inm.12738
|View full text |Cite
|
Sign up to set email alerts
|

Impact of suicide on health professionals in psychiatric care mental healthcare professionals' perceptions of suicide during ongoing psychiatric care and its impacts on their continued care work

Abstract: People who attempt suicide as well as those who actually take their own life often have communicated their suicidal thoughts and feelings to healthcare professionals in some form. Suicidality is one of the most challenging caring situations and the impacts of suicide care affect both the professional and personal lives of healthcare professionals. This study investigates how mental health professionals perceive suicide while providing psychiatric care and how this perception impacts their continued care work. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 32 publications
0
41
0
1
Order By: Relevance
“…Personally, I do not want to touch this memory anymore. (Zheng et al, 2019)I find it difficult to go to patients, especially in the evenings and early mornings because I do not want to step into a hanging… (Rytterström et al, 2020). After the patient committed suicide, I was mentally stimulated, in a trance, under great pressure, and once thought of quitting my job.…”
Section: Resultsmentioning
confidence: 99%
“…Personally, I do not want to touch this memory anymore. (Zheng et al, 2019)I find it difficult to go to patients, especially in the evenings and early mornings because I do not want to step into a hanging… (Rytterström et al, 2020). After the patient committed suicide, I was mentally stimulated, in a trance, under great pressure, and once thought of quitting my job.…”
Section: Resultsmentioning
confidence: 99%
“…Several psychiatric services offer psychological support after a patient's suicide, and healthcare professionals who had experienced a patient's suicide learned from that experience how to better manage suicide risk [26,27]. Healthcare professionals who had experienced a patient's suicide reported administering improved suicide risk assessments, felt better able to ask patients questions about suicidal ideation, and were more aware of suicide risk factors [28].…”
Section: Discussionmentioning
confidence: 99%
“…Awenat et al (2017) further reported that participants developed negative attitudes regarding the feasibility of preventing patient suicidal behavior. Lastly, Rytterström et al (2020) reported that the death of a patient by suicide led to questioning and a search for the meaning underlying the event.…”
Section: Resultsmentioning
confidence: 99%
“…The final dimension of personal impact was related to mental health outcomes including incidents of psychiatric or mental health diagnoses. Awenat et al (2017) and Rytterström et al (2020) identified that the emotional distress experienced in the aftermath of the patient suicidal behavior could be prolonged. Wang et al (2016), Goldstone and Bantjes (2019) and Moerman (2012) found that participants experienced emotional and physical exhaustion with the former two studies indicating that this experience could lead to burnout among mental health providers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation